2022
DOI: 10.1177/02697580221079993
|View full text |Cite
|
Sign up to set email alerts
|

Just an ‘optional extra’ in the ‘victim toolkit’?: The culture, mechanisms and approaches of criminal justice organisations delivering restorative justice in England and Wales

Abstract: Despite policy and guidance stating that all victims of crime should have ‘equal access’ to restorative justice in England and Wales, victim participation remains low. Here, the ways in which criminal justice agents – responsible for providing victim services, including restorative justice – offer restorative justice to victims are explored. Drawing upon empirical data collected from criminal justice organisations in two police force areas, this article outlines what factors lie behind the inconsistencies foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In accordance with the above, the impact of the structural understanding should preferably be minimized in this step. Instead, the victim's agency and empowerment as a support user become important aspects for the professional to keep in mind, in order not to just make decisions and assessments that do not align with how the victims perceive themselves (Banwell-Moore, 2023;Green et al, 2021;Thunberg, 2020). The victim's first contact with the support system plays a crucial role in the subsequent process.…”
Section: Combining Victimological and Organizational Perspectives On ...mentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with the above, the impact of the structural understanding should preferably be minimized in this step. Instead, the victim's agency and empowerment as a support user become important aspects for the professional to keep in mind, in order not to just make decisions and assessments that do not align with how the victims perceive themselves (Banwell-Moore, 2023;Green et al, 2021;Thunberg, 2020). The victim's first contact with the support system plays a crucial role in the subsequent process.…”
Section: Combining Victimological and Organizational Perspectives On ...mentioning
confidence: 99%
“…A Danish study found that some police officers deliberately refrain from informing victims about Victim Support Denmark (Offerrådgivningen) if they do not believe its services would be useful (e.g. based on the gender and age of the victim) (Banwell-Moore, 2023; Holmberg et al, 2020). Although this is possible, both due to the flexible nature of the guidelines for informing crime victims about the victim counseling service (i.e.…”
Section: Combining Victimological and Organizational Perspectives On ...mentioning
confidence: 99%
See 2 more Smart Citations
“…To protect victims from further violence, in many jurisdictions, these victimizations are categorically excluded from existing RP. Victim support workers and criminal justice personnel are often hesitant to inform victims of the existence of RP, but victims want to be informed, even if they choose not to use RP (Banwell-Moore, 2022; Van Camp and Wemmers, 2016). This limits the available options for these victims, and while the exclusion of cases of gender-based violence is intended to protect victims from secondary victimization, patronizing victims by limiting their choices may also contribute to a sense of revictimization (Wemmers, 2017).…”
Section: Rp and Victimsmentioning
confidence: 99%